STRATEGI PROMOSI KONSEP WISATA DIGITAL HOBBIT HOUSE MERAPI DI DAERAH ISTIMEWA YOGYAKARTA - Maria Ana Sila Hayatri; Omega Simanungkalit (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2023)
Hobbit House Merapi is one of the man-made tourist destinations in Sleman district, Special Region of Yogyakarta. This tourist destination has been around since 2016, but sales stopped in 2020 due to the Covid-19 pandemic. Since then, Hobbit House Merapi has been quiet from tourist visits. After re-opening in 2021, the management of this destination has not yet made a promotional plan that can bring many tourists to Hobbit House Merapi. Therefore, to increase the number of sales or to bring in many tourists to Hobbit House Merapi, a promotion strategy is needed. Currently, promotion can be done through technology that can be accessed by everyone anytime and anywhere. The digital concept promotion strategy is the answer to the current problem of Hobbit House Merapi.